PENGETAHUAN TEKNOLOGI DAN INFRASTRUKTUR DIGITAL TERHADAP TINGKAT PENGGUNAAN E-WALLET DI UMKM KOTA BAUBAU - Nur Zarliani Uli; Muh Azwar Anas; Fahlil Akbar Uli (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study examines the influence of technological knowledge and digital infrastructure on the level of E-Wallet and QRIS usage among Micro, Small, and Medium Enterprises (MSMEs) in Baubau City. The rapid development of digital payment systems has created opportunities for MSMEs to improve transaction efficiency, yet adoption remains uneven due to varying levels of technological understanding and infrastructure readiness. Using a quantitative approach, data were collected through Likert-scale questionnaires distributed to MSME respondents. The analysis employs multiple linear regression to measure the partial and simultaneous effects of the independent variables. The results are expected to show that technological knowledge—such as the ability to operate digital applications—and digital infrastructure, including internet quality and device availability, significantly influence the use of digital payment systems. This study contributes theoretically to digital finance adoption research and provides practical insights for MSMEs, local governments, and digital service providers in enhancing payment digitization